PENILAIAN KONDISI VISUAL JEMBATAN KUALA SAMBOJA dengan PEDOMAN PEMERIKSAAN JEMBATAN 2022 dan BRIDGE CONDITION RATING (BCR) - Cahyo Nugroho; Eswan, Eswan; Benny Mocthar (LPSDI Bina Patria, 2025)
Kuala Samboja Bridge is one of the main accesses connecting Samarinda - Kutai Kartanegara Regency. Judging from the visual condition of the bridge, it is necessary to conduct a visual condition inspection. This study aims to evaluate the condition of the Kuala Samboja Bridge through two approaches, namely the Bridge Inspection Guidelines method No. 01 / P / BM / 2022 and the Bridge Condition Rating (BCR) method. Based on the results of the visual assessment using the bridge inspection guidelines, a Condition Value of 3 was obtained, which indicates a severely damaged condition and requires immediate attention. On the other hand, the BCR method produces a value of 5.19 which indicates that the condition of the bridge is still relatively good (Good). In this analysis, the worst condition is the main reference for planning repair actions. The prediction of the bridge life based on Condition Value 3 shows a remaining service life of 9 years from a planned life of 50 years, while the equivalent of age approach based on the BCR value gives a remaining service life of 13 years. Recommended handling includes replacing joints (expansion joints), rehabilitating structural elements, and routine and periodic maintenance on piles. This handling plan is prepared referring to the general specifications of road and bridge construction work (Revision 2, 2018). From the calculation results, the total cost required for the maintenance and rehabilitation of the Kuala Samboja Bridge is Rp1,026,379,000.00. This study provides important recommendations for the management and extension of the service life of the bridge.